A legume-specific novel type of phytosulfokine, PSK-δ, promotes nodulation by enhancing nodule organogenesis. (9th February 2022) - Yu, Liangliang; Di, Qi; Zhang, Danping; Liu, Yumin; Li, Xiaolin; Mysore, Kirankumar S; Wen, Jiangqi; Yan, Junhui; Luo, Li
Abstract : A novel type of phytosulfokine, PSK-δ, and its precursor proteins from legume species play an important role in promoting legume nodulation by enhancing nodule organogenesis. Abstract: Phytosulfokine-α (PSK-α), a tyrosine-sulfated pentapeptide with the sequence YSO3 IYSO3 TQ, is widely distributed across the plant kingdom and plays multiple roles in plant growth, development, and immune response. Here, we report a novel type of phytosulfokine, PSK-δ, and its precursor proteins (MtPSKδ, LjPSKδ, and GmPSKδ1), specifically from legume species. The sequence YSO3 IYSO3 TN of sulfated PSK-δ peptide is different from PSK-α at the last amino acid. Expression pattern analysis revealed PSK-δ-encoding precursor genes to be expressed primarily in legume root nodules. Specifically, in Medicago truncatula, MtPSKδ expression was detected in root cortical cells undergoing nodule organogenesis, in nodule primordia and young nodules, and in the apical region of mature nodules. Accumulation of sulfated PSK-δ peptide in M. truncatula nodules was detected by LC/MS. Application of synthetic PSK-δ peptide significantly increased nodule number in legumes. Similarly, overexpression of MtPSKδ in transgenic M. truncatula markedly promoted symbiotic nodulation. This increase in nodule number was attributed to enhanced nodule organogenesis induced by PSK-δ. Additional genetic evidence from the MtPSKδ mutant and RNA interference assays suggested that the PSK-δ and PSK-α peptides function redundantly in regulating nodule organogenesis. These results suggest that PSK-δ, a legume-specific novel type of phytosulfokine, promotes symbiotic nodulation by enhancing nodule organogenesis.